Effect of milling time on mechanical properties of fly ash incorporated cement mortars - Zaldívar Cadena, Antonio Alberto; Díaz Peña, Ismael; González López, Javier Rodrigo; Vázquez Acosta, Francisco; Cruz López, Arquímedes; Vázquez Cuchillo, Odilón; Vázquez Rodríguez, Francisco Javier; Serrato Arias, Lucero Marisol (2013)
Abstract. Currently, thermal energy generation through coal combustion produces ash particles which cause serious environmental problems and which are known as Fly Ash (FA). FA main components are oxides of silicon, aluminum, iron, calcium and magnesium in addition, toxic metals such as arsenic and cobalt. The use of fly ash as a cement replacement material increases long term strength and durability of concrete. In this work, samples were prepared by replacing cement by ground fly ash in 10, 20 and 30% by weight. The characterization of raw materials and microstructure was obtained by Scanning Electron Microscopy (SEM) and X-ray diffraction (XRD). The final results showed that the grinding process significantly improves the mechanical properties of all samples when compared replacing a mortar made with cement by ground fly ash and the reference samples without added fly ash. The beneficial effect of the ground fly ash can increase the use of this product in precast concrete industry